Akt and SHIP modulate Francisella escape from the phagosome and induction of the Fas-mediated death pathway. - Murugesan V S Rajaram; Jonathan P Butchar; Kishore V L Parsa; Thomas J Cremer; Amal Amer; Larry S Schlesinger; Susheela Tridandapani (PLoS ONE)
Francisella tularensis infects macrophages and escapes phago-lysosomal fusion to replicate within the host cytosol, resulting in host cell apoptosis. Here we show that the Fas-mediated death pathway is activated in infected cells and correlates with escape of the bacterium from the phagosome and the bacterial burden. Our studies also demonstrate that constitutive activation of Akt, or deletion of SHIP, promotes phago-lysosomal fusion and limits bacterial burden in the host cytosol, and the subsequent induction of Fas expression and cell death. Finally, we show that phagosomal escape/intracellular bacterial burden regulate activation of the transcription factors sp1/sp3, leading to Fas expression and cell death. These data identify for the first time host cell signaling pathways that regulate the phagosomal escape of Francisella, leading to the induction of Fas and subsequent host cell death.